“Las percepciones del bullying en las violencias escolares” - Rosero Ponce, Nelly Violeta (2013)
Youth violence and adolescent manifests itself in different ways, one of which is known as the bullying (bullying among peers), a phenomenon that occurs with increasing intensity in the school, and that is a reflection of what happens every day in society. Speaking of violent situations in school contexts was associated with robberies, fights, destruction of materials of schools, but currently include other violent situations that have been made invisible or have not been recognized as a social problem, such is the case of bullying, which reflects a clear abuse of power exercise some subjects over others, where the protagonists are the children or adolescents, and that makes them victims and perpetrators of frequent attacks, causing serious consequences in the lives of those who suffer it, exercise it or observe it.